Βιβλιοκρισία:V. FOSKOLOU and S. KALOPISSI-VERTI (επιστ. επιμ.), Intercultural Encounters in Medieval Greece after 1204. The Evidence of Art and Material Culture (Byzantioς. Studies in Byzantine History and Civilization 19), Turnhout: Brepols 2022 - γερμανίδου σοφία (Byzantina Symmeikta, 2023)
Βιβλιοκρισία: V. Foskolou and S. Kalopissi-Verti (επιστ. επιμ.), Intercultural Encounters in Medieval Greece after 1204. The Evidence of Art and Material Culture (Byzantioς. Studies in Byzantine History and Civilization 19), Turnhout: Brepols 2022